Shear wave anisotropy in the upper mantle beneath the Aegean related to internal deformation - Hatzfeld, D.; Karagianni, E.; Kassaras, I.; Kiratzi, A.; Louvari, E.; Lyon-Caen, H.; Makropoulos, K.; Papadimitriou, P.; Bock, G.; Priestley, K. (Journal of Geophysical Research: Solid Earth, 2001)
Seismic anisotropy, deduced from SKS splitting measured at 25 stations installed in the Aegean, does not show a homogeneous pattern. It is not restricted to the North Anatolian Fault but is distributed over a region several hundreds kilometers wide. Little anisotropy is observed in continental Greece or along the Hellenic arc; however, significant anisotropy is observed in the north Aegean Sea. Large values of delay times suggest that anisotropy is due to a long path within the upper mantle and to strong intrinsic anisotropy. Our results, both in fast polarization directions and in values of delay time, do not support the idea that anisotropy is associated with inherited tectonic fabric nor are they consistent with the present-day Aegean motion relative to an absolute frame. In contrast, the direction of fast polarization and the magnitude of delay times correlate well with the present-day strain rate observed at the surface deduced from both geodetic measurements and seismicity. This anisotropy is not horizontally restricted to major surface faults but is spread over a wide region.